Graphene quantum dots (GQDs)-based nanomaterials for improving photodynamic therapy in cancer treatment - Fan, Hua-yang; Yu, Xiang-hua; Wang, Ke; Yin, Yi-jia; Tang, Ya-jie; Tang, Ya-ling; Liang, Xin-hua (European journal of medicinal chemistry, 2019)
Graphene quantum dots (GQDs) as novel nanomaterials, have received significant interest in the field of biomedical applications. It is worth noting that a large amount of research is devoted to GQDs-based nanocomposites for cancer treatment, especially for photodynamic therapy (PDT), in that they can act not only as more favorable photosensitizers (PSs) but also nanoplatforms for delivering PSs. In this review, the biological behavior and physicochemical properties of GQDs for PDT are described in detail, and the application of GQDs-based nanocomposites in improved PDT and PDT-based combination therapies is analyzed, which may provide a new strategy for designing efficient PDT systems for cancer treatment. [Display omitted] •The synthesis methods of GQDs have important effects on their physicochemical properties.•GQDs exhibit excellent biocompatibility and optical properties.•GQDs have great potential in photodynamic therapy.•PDT-based combination therapies show good synergistic effects.•Precisely tailoring properties of GQDs plays a key role in their application.